Using chitosan beads for removing heavy metals from car wash services - Tajuddin, Muhammad Farhan; Algheethi -, Adel Ali Saeed Abduh; Radin Mohamed, Radin Maya Saphira; Abdul Kadir, Aeslina (Penerbit UTHM, 2021)
Water pollution is one of the major pollutions in the era of globalization. Human activities such as industrial activities and construction waste are among the major factors that lead to and cause the pollution of water resources. However, the characteristics of car wash wastewater and Chitosan were discussed by comparing with previous treatment of wastewater to remove the contaminated materials to save the environment.